The Effectiveness of Implementing Webinar Tutorials for Primary School Mathematics Learning Subjects - Husnaeni; Lince, Ranak; Burga, Muhammad Alqadri (MIMBAR PGSD Undiksha, 2024)
Courses during the COVID-19 pandemic had to be carried out online. Meanwhile, not all students are ready to take part in online learning. The Webinar Tutorial (Tuweb) is designed to facilitate the implementation of online courses. This research aims to analyze the influence of implementing Tuweb on student learning outcomes. This type of research is ex post facto, with a mixed method (quantitative and qualitative) and a descriptive approach. This research sample was taken from the entire population of 70 students. The research subjects consisted of four tutors. Data collection techniques use observation, questionnaires, and documentation. The collected data was analyzed using descriptive-qualitative and descriptive-statistical techniques. The research results show that the implementation of Tuweb is in the very good category. Even though the tutor's course tool documents are not yet complete, the implementation of Tuweb shows that the tutor's performance is very good. Meanwhile, the implementation of Tuweb is in the very good category and has a perfect (very close) correlation with student learning outcomes. This research has implications for the importance of developing tutorial-based learning media so that course material can be accessed and studied by students anytime and anywhere.